Influence of storage solution on enamel demineralization submitted to pH cycling Influência da solução de armazenagem na desmineralização do esmalte submetido à ciclagem de pH - Juliana Silva Moura; Lidiany Karla Azevedo Rodrigues; Altair Antoninha Del Bel Cury; Emilena Maria Castor Xisto Lima; Renata Matheus Cunha Rodrigues Garcia (University of São Paulo, 2004)
Extracted human teeth are frequently used for research or educational purposes. Therefore, it is necessary to store them in disinfectant solutions that do not alter dental structures. Thus, this study evaluated the influence of storage solution on enamel demineralization. For that purpose, sixty samples were divided into the following groups: enamel stored in formaldehyde (F1), stored in thymol (T1), stored in formaldehyde and submitted to pH cycling (F2), stored in thymol and submitted to pH cycling (T2). All samples were evaluated by cross-sectional microhardness analysis and had their percentage of mineral volume versus micrometer (integrated area) determined. Differences between groups were found up to 30-µm depth from the enamel surface (p < 0.05), where samples from group T2 were more demineralized. It was concluded that the storage solution influenced the reaction of a dental substrate to a cariogenic challenge, suggesting that formaldehyde may increase enamel resistance to demineralization, when compared to demineralization occurring in enamel stored in thymol solution. Dentes humanos extraídos são freqüentemente utilizados para propósitos educacionais ou de pesquisa. Desta forma, é necessário o armazenamento dos mesmos em soluções desinfetantes que não alterem a estrutura dental. Para tanto, sessenta espécimes foram divididos nos seguintes grupos: esmalte armazenado em formol (F1), armazenado em timol (T1), armazenado em formol e submetido à ciclagem de pH (F2) e armazenado em timol e submetido à ciclagem de pH (T2), sendo avaliados por meio de análise de microdureza longitudinal e tiveram a porcentagem de volume mineral pro micrômetro determinada. Diferenças entre os grupos foram encontradas até a profundidade de 30µm da superfície do esmalte (p<0,05), onde o grupo mais desmineralizado era T2. Foi concluído que a solução de armazenagem influenciou na reação do substrato dental a um desafio cariogênico, sugerindo que o formaldeído pode aumentar a resistência do esmalte à desmineralização promovida pelo modelo de ciclagem de pH, quando comparado à desmineralização ocorrida no esmalte armazenado em timol.